Negative electrode containing lithium-alkaline earth metal alloy and lithium ion secondary battery containing the same

By employing a lithium-alkaline earth metal alloy as the negative electrode, the lithium-sulfur battery's lifespan and efficiency are improved, addressing issues of dendrite formation and decomposition.

JP2025507664AActive Publication Date: 2025-03-21LG ENERGY SOLUTION LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024549705
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-08-30
Filing Date
2023-08-31
Publication Date
2025-03-21
Estimated Expiration
2043-08-31

AI Technical Summary

Technical Problem

Lithium-sulfur batteries face challenges with lithium dendrite formation, porosity, and accelerated decomposition of LiPS and lithium salts, leading to reduced battery performance and lifespan.

Method used

A lithium-alkaline earth metal alloy is used as the negative electrode to stabilize lithium plating/elution, improve cell efficiency, and extend battery lifespan.

Benefits of technology

The use of a Li-M alloy negative electrode enhances the lifespan and Coulomb efficiency of lithium-sulfur batteries, maintaining a high discharge capacity during cycles and reducing decomposition reactions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025507664000001_ABST
    Figure 2025507664000001_ABST
Patent Text Reader

Abstract

The negative electrode includes a lithium-alkaline earth metal alloy, and the negative electrode can be used as a negative electrode for a lithium-sulfur battery. A lithium-sulfur battery using the alloy negative electrode has improved life characteristics and electrochemical performance such as coulombic efficiency. In particular, the capacity retention rate of the lithium secondary battery according to the present invention maintains a high discharge capacity during cycles.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a lithium-sulfur battery having improved battery performance, such as output and capacity.

[0002] This application claims priority to Korean Patent Application No. 10-2022-0110406 ​​filed on August 31, 2022, Korean Patent Application No. 10-2023-0100676 filed on August 1, 2023, and Korean Patent Application No. 10-2023-0114850 filed on August 30, 2023, and the contents disclosed in the specification and drawings of such applications are incorporated herein in their entirety. [Background technology]

[0003] Lithium-sulfur batteries have been attracting attention as high-energy density secondary batteries due to their light lithium anode and sulfur cathode with high discharge capacity. However, lithium metal anodes have the disadvantage of poor life characteristics due to the formation of lithium dendrites or porosity during the charge and discharge process of the battery. In addition, the growth of lithium dendrites and porosity increases the surface area of ​​the anode, accelerating the decomposition of LiPS (lithium polysulfide) and lithium salt on the surface of the anode, further deteriorating the performance of the lithium-sulfur battery. Therefore, uniform plating / elution induction of lithium and interface stabilization are essential to effectively improve the life of lithium-sulfur batteries.

[0004] Therefore, in the present invention, the negative electrode of a lithium-alkaline earth metal alloy is directly used as the negative electrode for a lithium-sulfur battery, thereby stabilizing the negative electrode plating / elution and improving the cell efficiency and lifespan. Summary of the Invention [Problem to be solved by the invention]

[0005] The present invention has been devised to solve the above problems, and has an object to provide a lithium secondary battery with an improved life.

[0006] Another object of the present invention is to provide a negative electrode that is prevented from deposition / dissolution during battery operation.

[0007] It is still another object of the present invention to provide a lithium ion secondary battery including the negative electrode.

[0008] Furthermore, the objects and advantages of the present invention can be realized by the means and combinations thereof recited in the claims. [Means for solving the problem]

[0009] The above technical problem can be solved by the features of the independent claims, and further embodiments can be explained by the features of the dependent claims and the detailed description of the invention.

[0010] A first aspect of the present invention relates to a negative electrode for a lithium secondary battery, the negative electrode comprising, as a negative electrode active material, a Li-M alloy including lithium (Li) and one or more metals M selected from alkaline earth metals.

[0011] According to a second aspect of the present invention, in the first aspect, the metal M is one or more selected from the group consisting of beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), and radium (Ra).

[0012] According to a third aspect of the present invention, in the first or second aspect, the metal M is strontium (Sr).

[0013] A fourth aspect of the present invention is any one of the first to third aspects, wherein in the Li-M alloy, a content ratio (wt%) of lithium (Li) to metal M is 99:1 to 90:10.

[0014] According to a fifth aspect of the present invention, in any one of the first to fourth aspects, the Li-M alloy contains metal M at a ratio of 0.10 mol % to 1.30 mol %.

[0015] According to a sixth aspect of the present invention, in any one of the first to fifth aspects, the Li-M alloy contains metal M at a ratio of 1 wt % to 10 wt %.

[0016] According to a seventh aspect of the present invention, in any one of the first to sixth aspects, the Li-M alloy is composed of lithium (Li) and one or more metals M selected from alkaline earth metals.

[0017] According to an eighth aspect of the present invention, in any one of the first to seventh aspects, the Li-M alloy is composed of lithium (Li) and a metal M selected from alkaline earth metals.

[0018] According to a ninth aspect of the present invention, in any one of the first to eighth aspects, the negative electrode contains 95 wt % or more of the Li-M alloy in 100 wt % of the negative electrode active material.

[0019] According to a tenth aspect of the present invention, in any one of the first to eleventh aspects, the negative electrode includes a Li-M alloy in the form of a metal thin film as a negative electrode active material layer.

[0020] According to an eleventh aspect of the present invention, in the tenth aspect, the negative electrode further includes a current collector.

[0021] The present invention also relates to a lithium secondary battery including a positive electrode, a negative electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte. A twelfth aspect of the present invention relates to such a lithium secondary battery, wherein the negative electrode is according to any one of the first to eleventh aspects.

[0022] According to a thirteenth aspect of the present invention, in the twelfth aspect, the electrolyte comprises a mixture of an acyclic ether and a cyclic ether, and the ratio of the acyclic ether to the cyclic ether in the mixture is a volume ratio (v / v) of 5:95 to 95:5.

[0023] According to a fourteenth aspect of the present invention, in the twelfth or thirteenth aspect, the lithium secondary battery is a lithium-sulfur battery in which the positive electrode active material contains sulfur (S8) or a sulfur (S) compound.

[0024] According to a fifteenth aspect of the present invention, in any one of the twelfth to fourteenth aspects, the lithium secondary battery has a capacity retention rate of 95% or more.

[0025] A sixteenth aspect of the present invention relates to a method for manufacturing a negative electrode for a lithium secondary battery according to any one of the first to eleventh aspects, the method including the steps of melting metallic lithium to obtain a first molten material, adding an alkaline earth metal to the obtained lithium molten material to obtain a second molten material, maintaining the second molten material at a temperature of 200° C. or higher to alloy the second molten material, and cooling the second molten material obtained in the alloying step to obtain a Li-M alloy.

[0026] According to a seventeenth aspect of the present invention, in the sixteenth aspect, the alloy is obtained in the form of an ingot, and the method further comprises the step of thinning the ingot into a plate-like structure of a predetermined thickness. Effect of the Invention

[0027] The Li-M alloy negative electrode according to the present invention can be used as the negative electrode of a lithium-sulfur battery. The lithium-sulfur battery incorporating the Li-M alloy into the negative electrode has the effect of improving the life characteristics and coulombic efficiency. In particular, the capacity retention rate of the lithium secondary battery according to the present invention maintains a high discharge capacity during cycles. In addition, the discharge capacity of the lithium secondary battery is improved. In addition, when the Li-M alloy is used as the negative electrode, uniform electrochemical plating / elution of lithium is induced, and decomposition of LiPS and lithium salt due to interfacial side reactions can be effectively suppressed.

[0028] The following drawings attached to this specification are for illustrating preferred embodiments of the present invention, and serve to further understand the technical idea of ​​the present invention together with the detailed description of the invention, so the present invention should not be interpreted as being limited to only the matters described in the drawings. In addition, the shape, size, scale, ratio, etc. of the elements in the drawings attached to this specification may be exaggerated in order to emphasize a clearer description. [Brief description of the drawings]

[0029] [Figure 1] The graph shows the cycle characteristics of the batteries produced in Examples 1 and 2 and Comparative Examples 1 to 4. In each of the Examples and Comparative Examples, the y-axis represents the discharge capacity (mAh / g) at 0.3 C, and the x-axis represents the number of cycles. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0030] The present invention will now be described in more detail.

[0031] The terms and words used in this specification and the claims should not be interpreted in a limited manner to their ordinary or dictionary meanings, but should be interpreted in a manner that corresponds to the technical concept of the present invention, based on the principle that the inventor himself can appropriately define the concept of the term in order to best describe the invention.

[0032] Unless otherwise limited, the detailed description defining or embodying the elements is applicable to all inventions and is not limited to the description of a particular invention, i.e., even if elements are disclosed individually in this specification, they may be considered to disclose an embodiment in which the elements are combined.

[0033] The terms used in this specification are used to describe specific embodiments and are not intended to limit the present invention. Unless otherwise specified in the context, the singular expressions include the plural expressions.

[0034] Furthermore, when the term "comprising" is used in the specification, it specifies the presence of stated features, integers, steps, operations, elements, components, or combinations thereof, and does not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components, or combinations thereof, unless specifically stated otherwise.

[0035] Throughout the specification, when a part "comprises," "contains," or "includes" a certain element, this does not mean excluding other elements, but may further include other elements, unless otherwise specified. The terms "comprise," "contain," and "include" expressly include the meanings of "consist of" and "essentially comprising," even if not expressly limited thereby.

[0036] As used herein, the term "essentially comprises" means "comprises at least 70%", preferably "comprises at least 80%", and most preferably "comprises at least 90%". When referring to the amounts of components of a mixture of substances, % means weight % relative to the total weight of each mixture, unless otherwise stated. For example, a material that essentially comprises polyethylene comprises polyethylene in an amount of 70% by weight or more, based on the total weight of the material.

[0037] As used throughout this specification, the terms "about," "substantially," and the like are used to mean a numerical value or a approximation thereof when given the inherent manufacturing and material tolerances in the stated sense, and are used to prevent unconscionable infringers from unfairly using disclosures in which precise or absolute numerical values ​​are recited to aid in the understanding of this application.

[0038] Throughout this specification, the phrase "A and / or B" means "A or B, or all of these."

[0039] In the present invention, the "specific surface area" is measured by the BET method, and specifically, can be calculated from the amount of nitrogen gas adsorbed at liquid nitrogen temperature (77K) using a BELSORP-mino II manufactured by BEL Japan.

[0040] As used herein, the term "polysulfide" refers to a polysulfide ion (S x 2- , x=8, 6, 4, 2) and Lithium polysulfide (Li2S x or LiS x - , x=8, 6, 4, 2) is a concept that includes both.

[0041] The term "composite" as used herein means a material in which two or more materials are combined to form physically and chemically distinct phases, thereby exhibiting a more effective function.

[0042] The term "porosity" as used herein means the ratio of the volume of pores to the total volume of a structure, and is expressed in units of "%" and may be used interchangeably with terms such as void ratio and porosity. In the present invention, the measurement of porosity is not limited to a specific method, and according to one embodiment, the porosity may be measured, for example, by the BET (Brunauer-Emmett-Teller) method using nitrogen gas or a mercury porosimeter and ASTM D-2873. In addition, the true density of the electrode may be calculated from the density (apparent density) of the electrode, the composition ratio of the materials contained in the electrode, and the density of each component, and the porosity of the electrode may be calculated from the difference between the apparent density and the true density (net density). For example, the porosity may be calculated according to the following formula 1.

[0043] formula 1 Porosity (volume%) = {1-(apparent density / true density)} x 100

[0044] The apparent density in the above formula 1 can be calculated from the following formula 2.

[0045] formula 2 Apparent density (g / cm 3 ) = (Weight of electrode (g)) / {(Thickness of electrode (cm)) × (Area of ​​electrode (cm 2 ))}

[0046] Apparent density, or bulk density, is a measure of how much space a material occupies per unit volume, including the voids or air spaces contained within it. That is, apparent density includes the material in its solid state and the voids within its volume. Apparent density can be calculated by dividing the mass of a material by its total volume, which includes all the pores and air spaces within the material. The formula for calculating apparent density is:

[0047] (Formula) Apparent density = mass / total volume

[0048] The mass may be measured using a balance. For materials with regular patterns (e.g., regular cubes, cylinders, etc.), the dimensions may be measured using suitable tools such as tape measures or calipers, which are known methods in the art. For samples with irregular patterns, the volume may be measured by measuring the displacement of the liquid to determine a known change in volume, which may be the same as the volume of the material. Those skilled in the art will be able to apply other known methods to measure the volume and apparent density.

[0049] Net density (true density) refers to the density of a material without taking into account any voids or porosity contained therein. It is the mass of a solid material divided by its actual volume, excluding any void space in said volume. True density may be calculated by dividing the mass of a material by the solid, unoccupied volume of the material. The formula for calculating true density is:

[0050] (Formula) True density = mass / solid volume (void volume is not taken into account)

[0051] Unlike apparent density, true density does not take into account the total volume not including voids and indicates the intrinsic density of a material. True density can be determined by the methods described above or using the gas pycnometer method according to ISO 12154:2014 or other measurement methods known to those skilled in the art.

[0052] In the present invention, "particle size D 50 " means the particle size at 50% of the volume cumulative particle size distribution of the particles. 50 can be measured using a laser diffraction method. For example, after dispersing particles in a dispersion medium, the particles are introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac MT 3000) and irradiated with ultrasonic waves of about 28 kHz at an output of 60 W to obtain a volume cumulative particle size distribution graph, and then the size of the particles that is 50% of the volume cumulative amount can be measured. Alternatively, in one embodiment of the present invention, the particle diameter D50 may be measured according to ISO 9276.

[0053] The thickness of the negative electrode can be measured using a known thickness measuring device when measuring the thickness of a battery element. For example, it can be measured using a contact type thickness measuring device such as a Mitutoyo handheld micrometer or a Stylus Profiler (Bruker, Dektak 150 Surface Profiler) or a rotary caliper (Maysun, RC-1W-200). For example, in the case of a stylus profiler, the measurement object is fixed to a sample stage so that the running direction of the tip and the surface of the measurement object are perpendicular, and the thickness can be measured by moving the stylus. In one embodiment, the stylus force is 5 mg and the measurement speed is 0.05 mm / s. Alternatively, in the present invention, the thickness of the negative electrode can be measured using a laser scan micrometer according to ASTM D374.

[0054] In addition, the size and thickness of each component in the drawings are arbitrarily illustrated for convenience of explanation, and the present invention is not limited to such illustration. In the drawings, the thicknesses are enlarged to clearly show a plurality of layers and regions. In the drawings, the thicknesses of some layers and regions are exaggerated for convenience of explanation.

[0055] negative electrode A first aspect of the present invention relates to a negative electrode active material for an electrochemical device and a negative electrode containing the same.

[0056] The negative electrode active material includes an alloy containing one or more metals M selected from alkaline earth metals and lithium. Preferably, the negative electrode includes an alloy of an alkaline earth metal and lithium as the negative electrode active material.

[0057] In one embodiment of the present invention, the negative electrode comprises a Li-M alloy, where Li is lithium and M is an alkaline earth metal, i.e., the negative electrode active material comprises an alloy, preferably an alloy composed of lithium and at least one metal M selected from alkaline earth metals.

[0058] In this specification, the term Li-M alloy is used to refer to an alloy of lithium and the metal M. The alkaline earth metal may belong to Group 2 of the periodic table. Preferably, the Li-M alloy is composed of lithium (Li) and a metal M selected from the alkaline earth metals.

[0059] In the present invention, the alkaline earth metal means beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), and radium (Ra). The metal M may include one or more selected from the group consisting of beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), and radium (Ra), preferably one or two, more preferably one. In the present invention, the metal M preferably includes strontium (Sr). Thus, at least one metal may be strontium (Sr). Most preferably, the metal M is strontium (Sr).

[0060] In one embodiment of the present invention, the content of the alkaline earth metal M may be 1 mol% or less relative to the total content of the Li-M alloy (100 mol%). The content of the alkaline earth metal M may be more than 0 mol% relative to the total content of the Li-M alloy (100 mol%). The content of the alkaline earth metal M may be 0.01 mol% to 1.30 mol%, 0.01 mol% to 1.0 mol%, 0.05 mol% to 0.95 mol%, 0.1 mol% to 0.90 mol%, 0.15 mol% to 0.85 mol%, 0.20 mol% to 0.80 mol%, 0.25 mol% to 0.75 mol%, or 0.25 mol% to 0.6 mol% relative to the total content of the Li-M alloy (100 mol%). Preferably, the alkaline earth metal may be included in an amount of 0.10 mol% to 1.30 mol%, or 0.30 to 1.0 mol%.

[0061] In one embodiment of the present invention, the lithium content in the alloy may be 99 mol% or more based on the total 100 mol% of the Li-M alloy. The alkaline earth metal content may be less than 100 mol% based on the total 100 mol% of the Li-M alloy. The lithium content based on the total 100 mol% of the Li-M alloy may be in the range of 98.7 mol% to 99.99 mol%, 99 mol% to 99.99 mol%, 99.05 mol% to 99.95 mol%, 99.1 mol% to 99.9 mol%, 99.15 mol% to 99.85 mol%, 99.2 mol% to 99.8 mol%, 99.25 mol% to 99.75 mol%, or 99.4 mol% to 99.75 mol% based on the total 100 mol% of the Li-M alloy. Preferably, the lithium metal content may be 98.70 mol% to 99.90 mol%, or 97.9 mol% to 99.9 mol%.

[0062] The upper and / or lower limits of the metal M may be adjusted within an appropriate range in consideration of the electrochemical characteristics of the battery to which the final negative electrode is applied. When the negative electrode contains the Li-M alloy within the above range, the life characteristics and Coulombic efficiency of the lithium secondary battery are improved. In particular, the capacity retention rate of the lithium secondary battery can maintain a high discharge capacity during cycling. In addition, the effect of improving the discharge capacity of the lithium secondary battery is achieved. If the alloy contains an excessive amount of alkaline earth metal M, the Coulombic efficiency may become unstable and the average efficiency value may become lower than that of a lithium metal negative electrode to which no alloy is applied. As a result, the capacity retention rate may decrease and the life characteristics may deteriorate.

[0063] In one embodiment of the present invention, the Li-M alloy may contain alkaline earth metal M in an amount exceeding 0 wt% based on 100 wt% of the total weight of the Li-M alloy. In one embodiment of the present invention, the Li-M alloy may contain metal M in an amount of 1 wt% to 10 wt% of the total alloy. Meanwhile, in terms of improving life characteristics and coulombic efficiency, the metal M may be contained in the alloy at 3 wt% or more, 5 wt% or more, or 7 wt% or more.

[0064] Specifically, when the above range is satisfied, the capacity retention rate of the lithium secondary battery can maintain a high discharge capacity over a long life span, and when the above range is satisfied, the discharge capacity of the lithium secondary battery can be increased.

[0065] On the other hand, if an excessive amount of metal M is included in the alloy, the coulombic efficiency may become unstable and the average efficiency value may be lower than that of a lithium metal anode to which no alloy is applied, so that the metal M may be preferably controlled to a range of 10 wt% or less relative to 100 wt% of the alloy. The weight percent (wt%) refers to the weight percent relative to 100 wt% of the total amount of the Li-M alloy. The upper and / or lower limits of the metal M may be controlled to an appropriate range in consideration of the electrochemical properties of the battery to which the anode is ultimately applied.

[0066] In one embodiment of the present invention, the Li-M alloy may contain 90 wt% or more and less than 100 wt% lithium (Li) based on 100 wt% of the total weight of the Li-M alloy. In one embodiment of the present invention, the Li-M alloy may contain 90 wt% or more, 93 wt% or more, or 95 wt% or more of lithium (Li) in the total alloy.

[0067] Specifically, when the above range is satisfied, the capacity retention rate of the lithium secondary battery can maintain a high discharge capacity over a long life span, and further, when the above range is satisfied, the discharge capacity of the lithium secondary battery can be increased.

[0068] On the other hand, when the lithium (Li) does not satisfy the above range, the coulombic efficiency is unstable and the average efficiency value may be lower than that of a lithium metal anode to which the alloy is not applied. The weight percent (wt%) refers to the weight percent relative to the total amount of the Li-M alloy, 100 wt%. The upper and / or lower limits of the lithium (Li) may be controlled to an appropriate range in consideration of the electrochemical characteristics of the battery to which the anode is ultimately applied.

[0069] Meanwhile, according to one embodiment of the present invention, the weight ratio (wt%) of Li:metal M in the Li-metal M alloy may have a value of 99:1 to 90:10, or 97:3 to 90:10, or 95:5 to 90:10, or 93:7 to 90:10. For example, it may be 99:1 to 95:5 or 93:7 to 97:3. The weight percentage of Li and metal M may be determined based on the total weight of lithium and metal M and / or the total weight percentage of the Li-M alloy. If the negative electrode includes a Li-M alloy within the above range, or is preferably composed of a Li-M alloy within the above range, the life characteristics and coulombic efficiency of the lithium secondary battery can be improved. In addition, a lithium-sulfur battery including the negative electrode can have an improved capacity retention rate that maintains a high discharge capacity even after repeated charging and discharging. On the other hand, if the amount of calcium alkaline earth metal M in the alloy is excessively greater than the above range, the coulombic efficiency may become unstable and may be lower than that of a lithium metal anode not using the alloy, i.e., the discharge capacity may decrease, the capacity retention rate may decrease, and the battery life may be shortened.

[0070] Meanwhile, in one embodiment of the present invention, the alloy Li-M may contain metal M in a ratio of 1 mol or less, for example, 0.075 to 0.90 mol, more specifically, 0.078 to 0.086 mol, per 100.00 mol of lithium.

[0071] In one embodiment of the present invention, the negative electrode may contain the Li-M alloy as a negative electrode active material in a range of 95 wt% or more, 95 wt% to 100 wt%, 98 wt% to 99.9 wt%, or 98 wt% to 99 wt%, for example, the negative electrode may be made of a Li-M alloy as a negative electrode active material.

[0072] Meanwhile, the negative electrode according to the present invention may be applied to a battery by preparing the Li-M alloy in a thin film form. That is, in the present invention, a Li-M alloy thin film may be used as the negative electrode active material layer. That is, the Li-M alloy may be a negative electrode in the form of a metal thin film. In one embodiment of the present invention, the thickness of the negative electrode active material layer may be 0.1 μm or more and 200 μm or less in terms of providing a sufficient lithium supply source for driving the battery and achieving high energy density. For example, the Li-M alloy thin film may have a thickness of 180 μm or less, or 160 μm or less, 150 μm or less, 140 μm or less, 130 μm or less, 120 μm or less, 110 μm or less, 100 μm or less, 80 μm or less, or 70 μm or less. Meanwhile, the thickness of the negative electrode active material layer may be 0.1 μm or more, 0.5 μm or more, 2 μm or more, 5 μm or more, 10 μm or more, 20 μm or more, 30 μm or more, 40 μm or more, 50 μm or more, 70 μm or more, 75 μm or more, or 90 μm or more. The Li-M alloy thin film may have a thickness of 0.1 μm to 180 μm. In a specific embodiment of the present invention, the Li-M alloy thin film may have a thickness of 40 μm to 80 μm, or 50 μm to 70 μm. In one embodiment of the present invention, the negative electrode may be formed by the Li-M thin film alone without a current collector, or by bonding a current collector and a Li-M alloy thin film.

[0073] Thus, the negative electrode may be constructed of a Li-M alloy, with or without a current collector optionally included.

[0074] The thickness of the negative electrode is the same as that described above. For example, the thickness can be measured using a thickness gauge made by Mitutoyo Corporation, but is not limited thereto. In the present invention, the thickness of the negative electrode can be measured using a laser scanning micrometer according to ASTM D374.

[0075] The Li-M thin film according to the present invention may be monolithic. The term "monolithic" means that there is no concentration gradient in the concentration of metal M in the Li-M thin film according to the present invention. Furthermore, the Li-M thin film according to the present invention may be substantially homogeneous. The Li-M thin film according to the present invention may be homogeneous. The Li-M thin film according to the present invention is a substantially homogeneous bulk material, where the entire bulk material is a continuous phase and homogeneous. That is, the metal M is all melted and the entire bulk is a continuous phase with lithium, and is in a completely homogeneous state.

[0076] In one embodiment of the present invention, the negative electrode current collector may be a negative electrode current collector commonly used in the art. For example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, or aluminum-cadmium alloy may be used. The negative electrode current collector may have a thickness of typically 3 μm to 500 μm, and like the positive electrode current collector, the surface of the current collector may have fine irregularities to enhance the binding force with the negative electrode active material. For example, the current collector may be used in various forms such as a film, sheet, foil, net, porous body, foam, or nonwoven fabric. For example, when a metal thin film type current collector is used, the current collector may have a thickness of 1 μm to 20 μm.

[0077] Meanwhile, the method for forming the Li-M thin film is not particularly limited, and any method for forming a layer or film commonly used in the art, such as a compression method or a coating method, may be used.

[0078] The Li-M thin film includes the steps of: a) melting metallic lithium to obtain a melt; b) adding metal M to the lithium melt obtained in step a) to obtain a lithium-M metal melt; c) maintaining the lithium-M metal melt obtained in step b) at a temperature of 200° C. or higher; d) cooling the lithium-M metal melt obtained in step c) to obtain lithium-M metal, preferably in the form of an ingot; and e) preparing a lithium-M metal alloy thin film from the lithium-M metal alloy in the form of an ingot.

[0079] The method may include placing a solid piece of lithium, such as a lithium ingot, together with a solid piece of M metal pellets in a suitable heating means (e.g., a vessel). The heating means may further include a stirring means for stirring the bimetallic melt and a means for providing an inert gas atmosphere to the heating means. The step a) of providing metallic lithium and M metal may not include a sputtering step, such as DC sputtering. Rather, the melting in step b) may include stirring the melt. The approach is more cost effective in providing a lithium-M metal alloy foil with a much more homogeneous and improved distribution of the M metal.

[0080] The melting may involve heating metallic lithium together with metal M at a temperature between 200°C and 500°C.

[0081] The cooling in step d) may be performed to room temperature, which may be about 20°C to 27°C, preferably 23°C to 25°C.

[0082] In one embodiment of the present invention, the method for producing the lithium-metal M thin film may include a method of roll-pressing a lithium-metal M alloy ingot to obtain a lithium-metal M thin film. In the roll-pressing, heat and pressure may be applied simultaneously, and may be performed using a hot roll press or the like.

[0083] Meanwhile, in one embodiment of the present invention, the method for preparing an electrode according to the present invention may further include the following step f) of bonding / adhering the lithium-metal M thin film obtained above to a current collector.

[0084] secondary battery A second aspect of the present invention relates to a lithium ion secondary battery including the negative electrode.

[0085] Positive electrode (lithium-sulfur battery) The lithium ion secondary battery may be a lithium-sulfur battery.

[0086] The positive electrode according to the present invention includes a current collector and a positive electrode active material layer disposed on at least one surface of the current collector.

[0087] The current collector can be any one used in the art, as long as it has electrical conductivity and is used as a current collector component. For example, the positive electrode current collector can be stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. The positive electrode current collector usually has a thickness of 3 μm to 500 μm, and it is also possible to form fine irregularities on the surface of the positive electrode current collector to increase the adhesive force of the positive electrode active material. The positive electrode current collector can be used in various forms, such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0088] In one embodiment of the present invention, the positive electrode active material layer includes a positive electrode active material, a conductive material, and a binder material, and may include 80 wt% to 97 wt% of the positive electrode active material, 2 wt% to 10 wt% of the conductive material, and 2 wt% to 10 wt% of the binder, based on the total weight of the positive electrode active material, the conductive material, and the binder material.

[0089] In the present invention, the positive electrode active material includes a sulfur-carbon composite. Preferably, the positive electrode active material includes 80 wt% or more, preferably 90 wt% or more of the sulfur-carbon composite relative to 100 wt% of the positive electrode active material, and more preferably, the positive electrode active material may be composed of only the sulfur-carbon composite. Also, the sulfur content is 70 wt% or more, preferably 80 wt% or more, relative to 100 wt% of the sulfur-carbon composite.

[0090] In one embodiment of the present invention, the sulfur-carbon composite may be a composite of the sulfur and the carbon material, or may be a coating or support having a core-shell structure. The core-shell coating may be a coating of either sulfur or the carbon material on the other material, for example, the surface of the carbon material may be surrounded by sulfur, or vice versa. The carbon material may have a porous structure having pores inside and on the surface of the body, and in particular, the internal pores may be filled with sulfur. The sulfur-carbon composite may be in any form as long as it satisfies the content ratio of the sulfur-based compound and the carbon material described below, and is not limited to the present invention. Meanwhile, in the present invention, the content of sulfur is preferably 70 wt % or more based on the total weight of the positive electrode active material.

[0091] The sulfur alone does not have electrical conductivity, and therefore is used in combination with a carbon material.

[0092] In one embodiment of the present invention, the sulfur is inorganic sulfur (S8), Li2S n (n≧1), disulfide compounds such as 2,5-dimercapto-1,3,4-thiadiazole, 1,3,5-trithiocyanuric acid, etc., organic compounds and carbon-sulfur polymers (C2S x ) n , x=2.5 to 50, n≧2). Preferably, inorganic sulfur (S8) may be included.

[0093] The carbon material has a porous structure including a plurality of pores on the surface and inside, and serves as a support that provides a framework for uniform and stable immobilization of sulfur, and compensates for the low electrical conductivity of sulfur to facilitate electrochemical reactions. In particular, the carbon material that serves as a sulfur support in the sulfur-carbon composite has a wide BET specific surface area and an appropriate particle size D 50 When the catalyst has a certain size, it is possible to increase the amount of sulfur supported, but at the same time, the irreversible capacity is low, and the energy density is increased, thereby increasing the utilization rate of sulfur during an electrochemical reaction.

[0094] In one embodiment of the present invention, the BET specific surface area of ​​the carbon material is at least 100 m 2 / g or more, up to 3,000m 2 In addition, or independently, the carbon material may have a primary particle diameter D 50 can be from 1 μm to 50 μm.

[0095] The BET specific surface area and particle size D of the carbon material 50 When the range is satisfied, sulfur can be uniformly dispersed on the inside and outside surfaces of the carbon material, while the irreversible capacity can be reduced and the electrochemical reactivity of sulfur can be increased. In addition, the use of the carbon material improves the electrochemical reactivity, stability, and electrical conductivity of the sulfur-carbon composite, thereby improving the capacity and life characteristics of the lithium-sulfur battery and showing optimal charge / discharge performance even if sulfur loss or volume change occurs during charge / discharge.

[0096] The particle diameter D of the primary particles 50 If the diameter of the primary particles is more than 50 μm, it is difficult for the lithium ions to move into the particles due to the limitations of mass transport, making it difficult to efficiently use the sulfur located in the center of the carbon. 50 If the particle size is less than 1 μm, it is difficult to increase the solid content because a large amount of solvent is required in the process of producing the electrode slurry, and sufficient pores between the particles are not secured, resulting in a decrease in output.

[0097] In the sulfur-carbon composite of the present invention, the carbon material used as the sulfur support can be generally prepared by carbonizing various carbon precursors.

[0098] Meanwhile, in one embodiment of the present invention, the pores of the carbon material may have a diameter of 0.5 nm to 200 nm based on the longest diameter. The carbon material is not particularly limited as long as it is spherical, rod-like, needle-like, plate-like, tubular or bulk-like and can be generally used in lithium-sulfur batteries.

[0099] The carbon material may be any porous and conductive carbon-based material commonly used in the art, and may include at least one selected from the group consisting of graphite, graphene, carbon black such as denka black, acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black, carbon nanotubes (CNTs) such as single-walled carbon nanotubes (SWCNTs) and multi-walled carbon nanotubes (MWCNTs), carbon fibers such as graphite nanofibers (GNFs), carbon nanofibers (CNFs), and activated carbon fibers (ACFs), graphite such as natural graphite, artificial graphite, and expanded graphite, carbon nanoribbons, carbon nanobelts, carbon nanorods, and activated carbon.

[0100] According to an embodiment of the present invention, the amount of the conductive material may be 0 to 30 wt % based on the total weight of the sulfur-carbon composite. For example, it may be 1 to 30 wt %, 15 to 30 wt %, or 20 to 30 wt %. If the content of the conductive material is lower than the above range, the electrons may not easily move between the positive electrode active material and the current collector, and the voltage and capacity may decrease. On the other hand, if it exceeds the above range, the relative proportion of the positive electrode active material may decrease, and the total energy (charge amount) of the battery may decrease. Therefore, it is preferable to determine an appropriate content within the above range.

[0101] In the sulfur-carbon composite according to the present invention, the sulfur is located on at least one of the inside and outside surfaces of the pores of the carbon material, and in this case, it may be present in an area of ​​less than 100%, preferably 1% to 95%, more preferably 60% to 90% of the entire inside and outside surfaces of the carbon material. When the sulfur is present on the surface of the carbon material within the above range, it can exhibit the maximum effect in terms of the electron transfer area and the wettability of the electrolyte. Specifically, since the sulfur is impregnated thinly and uniformly on the surface of the carbon material in the above range, it is possible to increase the electron transfer contact area during the charge and discharge process. If the sulfur is located in the area of ​​100% of the entire surface of the carbon material, the carbon material is completely covered with sulfur, which reduces the wettability of the electrolyte and the contact with the conductive material contained in the electrode, making it difficult to transfer electrons and unable to participate in the reaction.

[0102] In one embodiment of the present invention, the sulfur-carbon composite can be obtained by the following production method.

[0103] The method for producing the sulfur-carbon composite according to the present invention is not particularly limited and may be a method commonly known in the art, and may be prepared by a composite method including a step of (S1) mixing a carbon material with sulfur and a step of (S2) composite.

[0104] The mixing step (S1) is for increasing the degree of mixing of sulfur and the carbon material, and may be performed using a stirrer commonly used in the art. In this case, the mixing time and speed may be selectively adjusted according to the content and conditions of the raw materials.

[0105] The compounding method in step (S2) is not particularly limited in the present invention, and may be a method commonly used in the art. For example, a method commonly used in the art, such as dry compounding or wet compounding such as spray coating, may be used. For example, a method may be used in which the mixture of sulfur and carbon material obtained after mixing is heat-treated so that the molten sulfur is uniformly coated on the inside and outside surfaces of the carbon material. Meanwhile, in one embodiment of the present invention, a process of pulverizing the mixture of sulfur and carbon material by a method such as ball mill pulverization may be performed before the heat treatment. In one embodiment of the present invention, the heat treatment is performed at a temperature condition of 120° C. to 160° C. for about 20 minutes to 24 hours, and a heating device such as an oven may be used.

[0106] The sulfur-carbon composite prepared by the above-mentioned preparation method has a structure with a high specific surface area, a high sulfur loading, and an improved sulfur utilization rate. This not only improves the electrochemical reactivity of sulfur, but also improves the accessibility and contactability of the electrolyte, thereby improving the capacity and life characteristics of lithium-sulfur batteries.

[0107] Other cathode materials In one embodiment of the present invention, the positive electrode active material may be composed only of the sulfur-carbon composite, or may further include one or more additives selected from a transition metal element, a Group IIIA element, a Group IVA element, sulfur compounds of these elements, and alloys of these elements with sulfur.

[0108] In a specific embodiment of the present invention, the positive electrode active material layer may include a lithium transition metal composite oxide represented by the following Chemical Formula 1:

[0109] [Chemical formula 1] Li a Ni b Co c M 1 d M 2 e O2

[0110] In the above Chemical Formula 1, M 1 is Mn, Al or a combination thereof, and desirably may be Mn or Mn and Al.

[0111] Said M 2 is at least one selected from the group consisting of Zr, W, Y, Ba, Ca, Ti, Mg, Ta and Nb, preferably at least one selected from the group consisting of Zr, Y, Mg and Ti, more preferably Zr, Y or a combination thereof. 2 Although the elements are not essential, when contained in an appropriate amount, they can play a role in promoting grain growth during firing or improving the stability of the crystal structure.

[0112] Conductive material The conductive material is used to impart conductivity to the negative electrode, and can be used without any particular limitation as long as it has conductivity without inducing a chemical change in the battery to be constructed. Specific examples include graphite such as natural graphite and artificial graphite; carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, carbon fiber, carbon nanotube, and other carbon-based materials; metal powder or metal fiber such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and the like, and one or more of these may be used alone or in combination. The conductive material may be usually contained in an amount of 1 wt% to 30 wt%, preferably 1 wt% to 20 wt%, more preferably 1 wt% to 10 wt% based on the total weight of the negative electrode active material layer.

[0113] Binder Material The binder material serves to improve the adhesion between positive electrode active material particles and the adhesive strength between the positive electrode active material and the positive electrode current collector. Specific examples of the binder material include polyvinyllidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer rubber (EPDM rubber), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, and various copolymers thereof. One or a mixture of two or more of these may be used.

[0114] According to an embodiment of the present invention, the content of the binder may be 1 to 10 wt % based on the total weight of the positive electrode active material layer. If the content of the binder is lower than this range, the adhesive strength may decrease. If the content of the binder exceeds this range, the relative ratio of the positive electrode active material and the conductive material in the positive electrode may decrease, resulting in a decrease in battery capacity. Therefore, it is preferable to determine an appropriate content within this range.

[0115] electrode assembly Yet another aspect of the present invention relates to an electrode assembly including the negative electrode. The negative electrode may be as described above. The positive electrode may include the sulfur-carbon composite as a positive electrode active material. The electrode assembly includes a negative electrode, a positive electrode, and a separator interposed between the negative electrode and the positive electrode. For example, the separator may be interposed between the negative electrode and the positive electrode and stacked to form a stacked or stacked / folded type structure, or may be wound to form a jelly roll type structure. In addition, when a jelly roll structure is formed, a separator may be further disposed on the outside to prevent contact between the negative electrode and the positive electrode.

[0116] Separation membrane The separator is disposed in the electrode assembly in a manner interposed between the negative electrode and the positive electrode. The separator can be any separator that is commonly used as a separator in a lithium secondary battery by separating the negative electrode and the positive electrode and providing a passage for lithium ions to move. Specifically, the separator may be a porous polymer film, for example, a porous polymer film made of a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, or an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof. In addition, a typical porous nonwoven fabric, for example, a nonwoven fabric made of a high melting point glass fiber, a polyethylene terephthalate fiber, or the like, may be used. In addition, a separator coated with a coating layer containing a ceramic component or a polymer material may be used to ensure heat resistance or mechanical strength.

[0117] battery Yet another aspect of the present invention relates to an electrochemical device including the electrode assembly. The electrochemical device includes a battery case in which an electrode assembly and an electrolyte are housed together, and the battery case may be of any suitable type, such as a pouch type or a metal can type, that is commonly used in the art. The shape of the battery is not particularly limited, and may be of various shapes, such as a cylindrical shape, a stacked type, or a coin type.

[0118] electrolyte In the present invention, the electrolyte may include an organic solvent and a lithium salt.

[0119] The electrolyte may be an electrolytic solution containing a non-aqueous solvent that is a medium for the migration of ions involved in the electrochemical reaction of the lithium secondary battery, and a lithium salt that is an electrolyte.

[0120] In the present invention, the electrolyte may be an electrolytic solution containing a mixture of an acyclic ether and a cyclic ether.

[0121] In the present invention, the electrolyte may be an electrolytic solution in which the volume ratio of acyclic ether to cyclic ether is 5:95 to 95:5 (v / v).

[0122] In the present invention, the volume ratio (v / v) of the acyclic ether to the cyclic ether may be 5:95 to 95:5 (v / v). Specifically, it may be 80:20 to 20:80, more specifically 70:30 to 30:70, 60:40 to 40:60, for example, 50:50. In this specification, the volume ratio is the ratio of "volume % of non-cyclic ether" to "volume % of cyclic ether" in a mixture of the acyclic ether and the cyclic ether.

[0123] In a specific embodiment of the present invention, the volume ratio (v / v) of the acyclic ether to the cyclic ether may be 50:50 (v / v).

[0124] In a specific embodiment of the present invention, the volume ratio (v / v) of 1,3-dioxolane to dimethyl ether may be 5:95 to 95:5 (v / v).

[0125] Organic solvents The organic solvent serves as a medium that allows the movement of ions involved in the electrochemical reaction of the battery. As the organic solvent, any organic solvent that is commonly used in lithium secondary battery electrolytes may be used without limitation. For example, ethers, esters, amides, linear carbonates, cyclic carbonates, etc. may be used alone or in combination of two or more. Among these, ether-based compounds may be used as a representative example.

[0126] The ether-based compounds may include acyclic ethers and cyclic ethers.

[0127] For example, the acyclic ether may be at least one selected from the group consisting of dimethyl ether, diethyl ether, dipropyl ether, methyl ethyl ether, methyl propyl ether, ethyl propyl ether, dimethoxyethane, diethoxyethane, ethylene glycol ethyl methyl ether, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol methyl ethyl ether, triethylene glycol dimethyl ether, triethylene glycol diethyl ether, triethylene glycol methyl ethyl ether, tetraethylene glycol dimethyl ether, tetraethylene glycol diethyl ether, tetraethylene glycol methyl ethyl ether, polyethylene glycol dimethyl ether, polyethylene glycol diethyl ether, and polyethylene glycol methyl ethyl ether.

[0128] For example, the cyclic ethers include 1,3-dioxolane, 4,5-dimethyl-dioxolane, 4,5-diethyl-dioxolane, 4-methyl-1,3-dioxolane, 4-ethyl-1,3-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, 2,5-dimethoxytetrahydrofuran, 2-ethoxytetrahydrofuran, 2-methyl-1,3-dioxolane, 2-vinyl-1,3-dioxolane, 2,2-dimethyl-1,3-dioxolane, 2-methoxy-1,3-dioxolane, 2-ethyl-2-methyl-1,3-dioxolane, tetrahydropyran, 1,4-dioxane, 1,2-dimethoxybenzene, 1,3-dimethoxybenzene, 1,4-dimethoxybenzene, and isosorbide dimethyl ether. The thiophene may be at least one selected from the group consisting of, but is not limited to, furan, 2-methylfuran, 3-methylfuran, 2-ethylfuran, 2-butylfuran, 2,3-dimethylfuran, 2,4-dimethylfuran, 2,5-dimethylfuran, pyran, 2-methylpyran, 3-methylpyran, 4-methylpyran, benzofuran, 2-(2-nitrovinyl)furan, thiophene, 2-methylthiophene, 2-ethylthiophene, 2-propylthiophene, 2-butylthiophene, 2,3-dimethylthiophene, 2,4-dimethylthiophene, and 2,5-dimethylthiophene.

[0129] Examples of the ester of the organic solvent include, but are not limited to, any one selected from the group consisting of methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, γ-valerolactone, γ-caprolactone, σ-valerolactone, ε-caprolactone, and mixtures of two or more thereof.

[0130] Specific examples of the linear carbonate compound include, but are not limited to, any one selected from the group consisting of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate, ethyl methyl carbonate (EMC), methyl propyl carbonate, and ethyl propyl carbonate, or a mixture of two or more thereof.

[0131] Specific examples of the cyclic carbonate compound include ethylene carbonate (EC), propylene carbonate (PC), 1,2-butylene carbonate, 2,3-butylene carbonate, 1,2-pentylene carbonate, 2,3-pentylene carbonate, vinylene carbonate, vinylethylene carbonate, and halides thereof, or mixtures of two or more thereof. Examples of such halides include, but are not limited to, fluoroethylene carbonate (FEC).

[0132] Lithium salts The lithium salt is a compound capable of providing lithium ions in an electrolyte. Examples of such lithium salts include LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3CO2, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiCH3SO3, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiC4BO8, LiCl, LiBr, LiB 10 Cl 10 , LiI or LiB(C2O4)2 may be used. In the present invention, in order to increase the utilization possibility of sulfur and realize a high capacity and high voltage battery, it is preferable that the lithium salt includes Li-TFSI. More preferably, the lithium salt may include LiN(CF3SO2)2(Li-TFSI) in an amount of 80wt% or more, 90wt% or more, or 100% based on 100wt% of the total lithium salt.

[0133] The concentration of the lithium salt is in the range of 0.1M to 2.0M, preferably 0.5M to 1M, more preferably 0.5 to 0.75M. When the concentration of the lithium salt is within the above range, the electrolyte has appropriate conductivity and viscosity, so that it can exhibit excellent electrolyte performance and lithium ions can be effectively moved. When the concentration of the lithium salt is below the above range, it is difficult to ensure ion conductivity suitable for battery operation, and when the concentration of the lithium salt is above the above range, the viscosity of the electrolyte increases, so that the mobility of lithium ions decreases, or the decomposition reaction of the lithium salt itself increases, so that the performance of the battery may decrease.

[0134] In one specific embodiment of the present invention, in an electrolyte including a first solvent, a second solvent, and a lithium salt, the molar ratio of the lithium salt to the second solvent to the first solvent may be 1:0.5-3:4.1-15. In addition, in one embodiment of the present invention, the molar ratio of the lithium salt to the second solvent to the first solvent may be 1:2:4-13, or 1:3:3-10, or 1:4:5-10, and the electrolyte included in the lithium-sulfur battery of the present invention may include a first solvent including a fluorine-based ether compound at a higher content ratio than the second solvent including a glyme-based compound.

[0135] Other additives In addition to the electrolyte components, the electrolyte may further contain additives for the purpose of improving the life characteristics of the battery, suppressing the capacity reduction of the battery, improving the discharge capacity of the battery, etc. For example, the additives may be nitric acid compounds, nitrous acid compounds, haloalkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, aluminum trichloride, etc., which may be used alone or in combination. The additive may be included in an amount of 0.1 wt% to 10 wt%, preferably 0.1 wt% to 5 wt%, or 0.5 wt% to 4 wt%, 0.7 wt% to 3 wt%, 0.9 wt% to 2 wt%, or 0.95 wt% to 1.5 wt%, based on the total weight of the electrolyte.

[0136] In a specific embodiment of the present invention, the electrolyte may include a nitrate compound and / or a nitrite compound as an additive. The nitrate compound / nitrite compound forms a stable coating on the lithium metal electrode, which is the negative electrode, and thus improves charge / discharge efficiency. The nitric acid or nitrite-based compound may include, but is not limited to, one or more selected from the group consisting of inorganic nitric acid or nitrite compounds such as lithium nitrate (LiNO3), potassium nitrate (KNO3), cesium nitrate (CsNO3), barium nitrate (Ba(NO3)2), ammonium nitrate (NH4NO3), lithium nitrite (LiNO2), potassium nitrite (KNO2), cesium nitrite (CsNO2), and ammonium nitrite (NH4NO2); organic nitric acid or nitrite compounds such as methyl nitrate, dialkylimidazolium nitrate, guanidine nitrate, imidazolium nitrate, pyridinium nitrate, ethyl nitrate, propyl nitrate, butyl nitrate, pentyl nitrate, and octyl nitrate; and organic nitro compounds such as nitromethane, nitropropane, nitrobutane, nitrobenzene, dinitrobenzene, nitropyridine, dinitropyridine, nitrotoluene, and dinitrotoluene, and combinations thereof. In a preferred embodiment of the present invention, the additive may include lithium nitrate.

[0137] In one embodiment of the present invention, the capacity retention of the lithium secondary battery according to the present invention may be 95% or more. The capacity retention may be measured at about 25° C. The capacity retention may be measured at 100 to 200 cycles, for example, 120 charge / discharge cycles, at 0.3C. The battery may be activated by 3 charge / discharge cycles at 0.1C and 2 charge / discharge cycles at 0.2C at 25° C. before measuring the capacity retention. The capacity retention may be measured in the range of 1.8V to 2.7V. In one embodiment, the capacity retention may be measured for a lithium-sulfur battery, and in this case, a person skilled in the art may adjust the measurement method accordingly.

[0138] Capacity retention is the measurement of how well a battery or energy storage device maintains its initial capacity over time. It can be an indicator of a battery's long-term performance and lifespan. Capacity retention is usually expressed as a percentage and can be calculated by comparing the battery's current capacity to its initial (or maximum) capacity.

[0139] The capacity retention rate can be calculated at each measurement point using the following formula:

[0140] Capacity retention rate (%) = (subsequent capacity / initial capacity) x 100 Here, the "subsequent capacity" is the capacity measured after cycling or aging, and the "initial capacity" is the initial capacity measured before the start of the test. The capacity measured by cycle is shown in FIG. 1. The initial capacity may be the capacity of the first cycle after activation by three charge / discharge cycles at 0.1C and two charge / discharge cycles at 0.2C at 25°C. The initial capacity may be measured at 0.3C for charging and discharging. The subsequent capacity may be measured 100 to 200 cycles, for example, 120 cycles, after the initial cycle, and preferably 120 charge / discharge cycles at 0.3C. It is desirable that the capacity retention rate is 95% or more for each of the subsequent cycles after the 120 cycles, if possible. Furthermore, in other embodiments, the capacity retention rate may be 95% or more and less than 100% (e.g., 99% or less) for the subsequent cycles after the average of 120 cycles.

[0141] In one embodiment of the present invention, the average coulombic efficiency of the lithium secondary battery is 98% or more. The coulombic efficiency of the battery may be measured at 25° C. with 0.2 C charge / 0.3 C discharge. The average coulombic efficiency may be calculated from an average of 100 to 200 cycles, for example, 120 or 150 cycles, of the battery. Also, one cycle may be from SOC (state of charge) 100 to SOC 0. Therefore, the average coulombic efficiency may be measured at 25° C. with 0.2 C charge / 0.3 C discharge for 100 to 200 cycles, for example, 120 or 150 cycles. In a specific embodiment of the present invention, the battery for measuring the average coulombic efficiency may be manufactured by stacking a total of seven positive electrodes and eight negative electrodes with separators sandwiched therebetween.

[0142] The present invention also provides a battery module including the lithium-sulfur battery as a unit cell, which can be used as a power source for medium to large devices that require high temperature stability, long cycle characteristics, and high capacity characteristics.

[0143] Examples of the medium- to large-sized devices include, but are not limited to, power tools powered by electric motors; electric vehicles, including electric vehicles (EVs), hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), and the like; electric two-wheeled vehicles, including electric bicycles (E-bikes) and electric scooters (Escooters); electric golf carts; and power systems.

[0144] Hereinafter, preferred embodiments of the present invention will be described to aid in understanding the present invention. However, the following embodiments are merely illustrative of the present invention, and it will be apparent to those skilled in the art that various modifications and alterations are possible within the scope of the scope and technical ideas of the present invention. Of course, such modifications and alterations are included in the scope of the appended claims.

[0145] [Example] Anode production Li metal was put into a heating furnace and melted by applying heat at a temperature of 200°C to 500°C. Metal M pellets were then put into the furnace in the ratio shown in Table 1 below and melted. The furnace was then maintained at 200°C to 500°C and stirred. The resultant was cooled to form a Li-M alloy ingot. The ingot was extruded and rolled to a thickness of 60 μm to manufacture a negative electrode.

[0146] [Table 1]

[0147] ICP analysis results of alloys The alloys obtained in each Example and Comparative Example were immersed in a hydrochloric acid peroxide solution to dissolve the surface to a thickness of 1 μm, and the resulting solution was analyzed using an inductively coupled plasma mass spectrometer (Perkin Elmer, OPTIMA 7300DV). Table 2 below shows the particle amount (wt%) of each element in each lithium (Li)-M alloy. There may be slight differences in the measured amounts from Table 1 depending on the sample preparation method of the inductively coupled plasma mass spectrometer. As a result, each component was confirmed to be in an amount corresponding to the component ratio added during the production of the alloys of each Comparative Example and Example.

[0148] [Table 2]

[0149] Battery manufacturing Carbon nanotubes and sulfur were uniformly mixed (sulfur:carbon nanotubes = 75wt%:25wt%) and placed in an oven at 155°C for 30 minutes to prepare a sulfur-carbon composite. The sulfur content in the 100wt% sulfur-carbon composite was 75wt%. 90wt% of the prepared sulfur-carbon composite, 5wt% of denka black, and 5wt% of a binder (styrene butadiene rubber / carboxymethyl cellulose, 7:3 weight ratio) were mixed to prepare a slurry for preparing a positive electrode. The solid content in the slurry was 25wt%. The slurry was applied to both sides of a 20μm thick aluminum current collector, dried at 50°C for 12 hours, and pressed using a roll press to prepare a positive electrode. The load of the positive electrode active material was 5.4mAh / cm 2 The porosity of the positive electrode active material was 68 vol%. The porosity of the positive electrode active material was measured according to the following formula 1.

[0150] [Formula 1] Porosity (volume%) = {1-(apparent density / true density)} x 100

[0151] In the above formula 1, the apparent density can be calculated from the following formula 2.

[0152] [Formula 2] Apparent density (g / cm 3 ) = (Weight of electrode (g)) / {(Thickness of electrode (cm)) × (Area of ​​electrode (cm 2 ))}

[0153] The electrolyte used was a mixture of 1M lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and 1 wt% lithium nitrate (LiNO3) dissolved in an organic solvent consisting of 1,3-dioxolane and dimethyl ether (DOL:DME = 1:1 (volume ratio)).

[0154] The prepared positive and negative electrodes were placed facing each other, and a polyethylene porous film with a thickness of 16 μm and a porosity of 68 vol% was placed between them as a separator, and then the resultant was placed in a pouch, and the prepared electrolyte was injected and sealed to prepare a lithium-sulfur battery. The battery was constructed by stacking and folding a total of seven positive electrodes and eight negative electrodes with the separator sandwiched therebetween.

[0155] Electrochemical properties evaluation results The fabricated battery was activated by charging and discharging at 0.1C for 3 cycles and at 0.2C for 2 cycles at 25° C., and then operated at 0.3C for 120 cycles to confirm cycle characteristics and efficiency.

[0156] FIG. 1 shows the specific discharge capacity (mAh / g) of the batteries manufactured in the examples and comparative examples. Table 3 below shows the capacity retention and discharge capacity of each of the examples and comparative examples. The capacity retention and discharge capacity are shown after 120 cycles and 6 cycles, including 5 driving cycles for activation. In addition, if the capacity retention after 120 cycles at 0.3C exceeds 1,000mAh / g, the example or comparative example is indicated with "+", and if the capacity retention after 120 cycles at 0.3C is less than 1,000mAh / g, the example or comparative example is indicated with "-".

[0157] According to FIG. 1 and Table 3, it was confirmed that the batteries of Examples 1 and 2 had excellent specific capacity characteristics compared to the batteries of Comparative Examples. Meanwhile, Comparative Example 2 had similar discharge capacity and life characteristics to Comparative Example 1. This is believed to be because the content of metal M was low and the effect of the alloy was not exhibited. Meanwhile, Comparative Example 3 contained too much Sr, and therefore showed a lower discharge capacity and poor life characteristics compared to Comparative Example 1. Meanwhile, it was confirmed that Comparative Example 4 showed a higher discharge capacity than Comparative Example 1, but had a deteriorated life characteristic compared to the alloy containing Sr.

[0158] Furthermore, the discharge capacities of Examples 1 and 2 were maintained at 1,000 mAh / g or more even after 120 cycles, whereas the discharge capacities of Comparative Examples 1, 2, 3, and 4 decreased to less than 1,000 mAh / g after 120 cycles. Thus, Examples 1 and 2 exhibited improved capacity retention rates due to their high discharge capacities, and were maintained at a high level even after repeated charge / discharge (120 cycles).

[0159] [Table 3]

Claims

1. The negative electrode for a lithium secondary battery comprises a Li-M alloy containing lithium (Li) and one or more metals M selected from alkaline earth metals.

2. 2. The negative electrode for a lithium secondary battery according to claim 1, wherein the metal M is one or more selected from the group consisting of beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), and radium (Ra).

3. 2. The negative electrode for a lithium secondary battery according to claim 1, wherein the metal M is strontium (Sr).

4. 2. The negative electrode for a lithium secondary battery according to claim 1, wherein in the Li-M alloy, the content ratio (wt%) of lithium (Li) to metal M is 99:1 to 90:

10.

5. 2. The negative electrode for a lithium secondary battery according to claim 1, wherein the Li-M alloy contains metal M in a proportion of 0.10 mol % or more and 1.30 mol % or less.

6. 2. The negative electrode for a lithium secondary battery according to claim 1, wherein the Li-M alloy contains metal M at a ratio of 1 wt % or more and 10 wt % or less.

7. 2. The negative electrode for a lithium secondary battery according to claim 1, wherein the Li-M alloy is composed of lithium (Li) and one or more metals M selected from alkaline earth metals.

8. 2. The negative electrode for a lithium secondary battery according to claim 1, wherein the Li-M alloy is composed of lithium (Li) and a metal M selected from alkaline earth metals.

9. 2. The negative electrode for a lithium secondary battery according to claim 1, wherein the negative electrode contains 95 wt % or more of the Li-M alloy in 100 wt % of the negative electrode active material.

10. 2. The negative electrode of claim 1, wherein the negative electrode comprises a Li-M alloy in the form of a metal thin film as a negative electrode active material layer.

11. The negative electrode for a secondary battery according to claim 10 , wherein the negative electrode further comprises a current collector.

12. A lithium secondary battery comprising a positive electrode, a negative electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte, wherein the negative electrode is the one according to any one of claims 1 to 11.

13. The lithium secondary battery according to claim 12, wherein the electrolyte is an electrolytic solution containing a mixture of a cyclic ether and an acyclic ether, and the acyclic ether and the cyclic ether are contained in the electrolytic solution in a volume ratio of 5:95 to 95:

5.

14. The lithium secondary battery has a positive electrode active material of sulfur (S 8 13. The lithium secondary battery according to claim 12, which is a lithium-sulfur battery containing a sulfur (S) compound.

15. 13. The lithium secondary battery according to claim 12, wherein the capacity retention rate of the lithium secondary battery is 95% or more.

16. A method for producing a negative electrode for a lithium secondary battery according to any one of claims 1 to 11, comprising the steps of: Melting metallic lithium to obtain a first melt; adding an alkaline earth metal to the first molten material to obtain a second molten material; maintaining the second molten material at a temperature of 200° C. or more to alloy the second molten material; and cooling the second molten material obtained in the alloying step to obtain a Li-M alloy.

17. The method for manufacturing a negative electrode for a lithium secondary battery according to claim 16, further comprising the step of obtaining the alloy in an ingot form and thinning the ingot into a plate-like structure having a predetermined thickness.

Citation Information

Patent Citations

  • Multi-element lithium-magnesium alloy negative electrode material for high-cycle-stability secondary battery and adaptive electrolyte thereof

    CN110797524A

  • Lithium alloy negative electrode for secondary battery

    JP1994036763A

  • Negative electrode for lithium secondary battery

    JP1997161774A

  • Lithium-sulfur secondary battery

    JP2022528412A